2002
DOI: 10.1108/03699420210449043
|View full text |Cite
|
Sign up to set email alerts
|

Formation and the colour development in cobalt spinel pigments

Abstract: Nanocrystalline cobalt spinels were synthesized under hydrothermal conditions, starting from metal chlorides. The color properties in these systems mainly depend upon the preparative method and cation distributions, which have been determined by X-ray powder diffraction using Rietveld refinements and visible near infrared absorption spectra. We observe the influence of tetrahedral and octahedral preference of cations such as Co 2+ , Cr 3+ , Mn 3+ upon the formation and the color development of cobalt spinel pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Spinel-type oxide materials have attracted a great deal of attention from scientists and industry leaders because of their relevant magnetic, refractory and semiconducting properties [1,2]. The spinel structure, featuring the general formula AB 2 O 4 displays 64 tetrahedral sites and 32 octahedral sites, of which only 8 tetrahedral sites and 16 octahedral sites are occupied by the cations A 2þ and B 3þ , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Spinel-type oxide materials have attracted a great deal of attention from scientists and industry leaders because of their relevant magnetic, refractory and semiconducting properties [1,2]. The spinel structure, featuring the general formula AB 2 O 4 displays 64 tetrahedral sites and 32 octahedral sites, of which only 8 tetrahedral sites and 16 octahedral sites are occupied by the cations A 2þ and B 3þ , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Natural spinels are frequent in most geological environments and occur as main or accessory minerals in different rocks in the Earth's lower crust and upper mantle. Being the cation distribution highly sensitive to temperature, pressure, oxygen fugacity, and bulk rock and fluid compositions, its full knowledge is extremely useful for constructing mineral geothermometers, geobarometers, and oxygen fugacity sensors for petrologic studies.…”
Section: Introductionmentioning
confidence: 99%
“…During this process, hydroxides are formed and counteract the formation of corrosion due to the higher pH, the formation of soaps of alkaline earth metals in some binders (alkyds, epoxy esters), and passivation brought about by the presence of OH-ions. [5][6][7][8][9] The goal of this paper is to study the effect of different single-, double-, and triple-cation ferrite pigment loadings in anticorrosive paint formulations based on medium oil alkyd resin. The tests revealed that the best loading of these pigments was 15% of the total pigments, and a very high inhibition effect was exhibited while using these pigments.…”
Section: Introductionmentioning
confidence: 99%